Studens' Perceptions of English Club in Enhancing Speaking Skill - Maria Fridolin Naben; Anselmus Sahan (Universitas Muhammadiyah Tangerang, 2025)
This study explores students’ perception of English Club as a platform for enhancing their speaking skills. The English Club provides a supportive and interactive environment where students can improve their speaking skills through group discussions, role playing, interactive game, storytelling and presentation. This study was conducted at English Club of English Study program, Universitas Timor. Using a descriptive qualitative approach, the data were collected through observation and interviews with 5 students who actively participate in the English Club. The findings presented that most students perceive the English Club as beneficial in improving their speaking ability especially in pronunciation, fluency and vocabulary. Additionally, students appreciate the informal learning atmosphere which reduce their fear and anxiety in speaking. This study concludes English teachers can improve students’ English language proficiency by implementing or developing the English Club's teaching methodology and creating a more relaxed and enjoyable learning atmosphere.